Time use in the city and labor productivity: Distribution patterns of work, transportation and leisure - Arroyo Laguna, Juan (2015)
The study examines the patterns of time use in Metropolitan Lima, its deciding factors and the reciprocal influence among times, based on the National Time Use Survey. A typology of working hours in the city is identified, with particular mixtures of time uses, some with efficient time uses and some without, in an urban environment without planned time management. Three main use patterns are recognized: adult workers, women devoted to household chores and single men. It is proven that work time is affected mainly by income level and age, travel time by main occupation, and free time by age. It is confirmed that the population spends time outside of work in activities that do not necessarily imply rest. The individual margins for an optimum time management are narrow. The contrast between the results with the literature on the topic reveals a lot of similarities but also differences.